Strategic Development of Multidisciplinary-Based Islamic Education Curriculum: Approaches and Implications - Etika Pujianti; Subagiyo Subagiyo; Siti Salbiah; Dewi Nisrina; Hairul Fahmi; Ihsan Saifullah (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2026)
This study aims to explore the strategic development of a multidisciplinary-based Islamic education curriculum, focusing on the approaches and implications for effective educational practices. The problem addressed is the challenge of integrating various disciplines within the Islamic education curriculum while maintaining the core values and objectives of Islamic teachings. The research adopts a qualitative case study approach, utilizing interviews, focus group discussions, and document analysis as data collection instruments. Data analysis follows the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that the integration of multiple disciplines within Islamic education enhances students' critical thinking, problem-solving skills, and broader knowledge application. Teachers face challenges in adapting traditional teaching methods to interdisciplinary approaches, requiring ongoing professional development and curriculum support. The curriculum development process must consider local cultural contexts and the specific needs of students, ensuring relevance and engagement. Collaborative efforts between educational institutions, scholars, and policymakers are crucial to successfully implementing multidisciplinary-based Islamic education. Additionally, there is a need for further research to explore the long-term impact of such a curriculum on students' academic and personal development. Future studies should focus on evaluating the effectiveness of the multidisciplinary approach in various educational settings.